Mapping The Effectiveness Of Restorative Justice Through Rehabilitation In Handling Drug Abuse Cases - Nurhaliza B., Siti; Kaluku, Julisa Aprilia; Puluhulawa, Irlan (Universitas Negeri Gorontalo, 2024)
The purpose of this research is to describe the effectiveness of restorative justice through rehabilitation in drug abuse cases at the Gorontalo Provincial BNN, as well as to identify the inhibiting factors. This research uses empirical legal approach with descriptive method, conducted at the Office of National Narcotics Agency of Gorontalo Province. Data were collected through interviews, literature review, and documentation, with qualitative data analysis. The results showed that restorative justice through rehabilitation has not been fully effective, as indicated by drug abusers who still use drugs again after rehabilitation. The inhibiting factors include internal aspects such as the patient's lack of determination and external aspects such as inadequate facilities and infrastructure and negative stigma from the community